Assessment of the current status of area enclosures and their livelihood contribution in Wag-Lasta areas, north-eastern Ethiopia - Amerra, Yekoye Alene; Shumie, Abebe; Worie, Birhan; Lamesgin, Haymanot; Wondie, Menale; Belay, Beyene; Asmare, Silesh; Nigusie, Girma; Ebabu, Adino; Eshetie, Mubarek (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Several studies have shown that keeping areas free from animal contact can not only restore degraded areas but also improve benefits to local communities. This survey aimed to identify the changes brought in the area enclosures after enclosure, the benefits they are giving to the users, and the current constraints of area enclosures in the Wag-Lasta area. A simple random sampling method was used to select respondents. A total of 180 respondents, from users of the area enclosure, participated. The data were analyzed by descriptive statistics using the SPSS tool version 26. According to the result, the majority of the respondents (74.4%) said that area enclosures were effective in the rehabilitation of degraded lands, and confirmed that they were beneficial for soil erosion control, the development of water sources, the conservation of natural resources (soil, water, trees, and shrubs), and the regeneration of trees and shrubs. The results also showed that the local community got different benefits from area enclosures, like animal fodder (53.3%), bee pollen sources (23.3%), and reducing soil erosion (23.3%). The local community also gained, on average, 4102.3 ETB and 1018.18 ETB per annum from grass and fuelwood selling, respectively, from area enclosures. Despite all these benefits, respondents explained that area enclosures were under critical problem due to free grazing (49.4%); flooding (28.9%); and illegal cuttings (21.6%). Hence, to minimize the existing constraints and improve the sustainability of benefits from area enclosure, it is important to diversify benefits, create awareness, and introduce new technologies related to sources of better fuelwood and animal fodder, as well as strengthen local communities.